Constitutive modeling for the accurate characterization of the tension behavior of PEEK under small strain. (August 2018) - Chang, Baoning; Wang, Xinyu; Long, Zhiqiang; Li, Zheng; Gu, Junfeng; Ruan, Shilun; Shen, Changyu
Abstract: To accurately characterize the tension behavior of Poly-ether-ether-ketone (PEEK) under small strain is essential to predict the mechanical properties of the PEEK and PEEK-based composites. Therefore, the uniaxial tensile responses of PEEK prior to necking are studied at strain rates ranging from 10 −5 s −1 to 10 −1 s −1 and temperatures ranging from −60 °C to 140 °C. The tensile responses exhibit nonlinear characteristics and the dependence of temperature and strain rate. With temperature increasing, the yield stress and yield strain of PEEK dramatically decrease while the modulus decreases slightly. Based on the uniaxial tensile results, a phenomenological nonlinear viscoelastic constitutive model is proposed to characterize the stress-strain of PEEK before yielding considering temperature and strain rate dependence, and the model is used to predict the tensile behavior of PEEK. The results indicate the proposed constitutive model can accurately predict the nonlinear tensile stress-strain responses and the yield stress of PEEK over a wide range of temperatures under small strain. Highlights: The tensile behavior of PEEK prior to yielding was studied. The effects of strain rate and temperature were investigated. The test temperature encompasses a wide range of temperatures-60 °C to 140 °C. A nonlinear viscoelastic constitutive model for PEEK was presented. The tensile stress strain responses and the yield stress were predicted and validated.